360 Degrees of Facial Perception: Congruence in Perception of Frontal Portrait, Profile, and Rotation Photographs - Třebický, Vít; Fialová, Jitka; Stella, David; Štěrbová, Zuzana; Kleisner, Karel; Havlíček, Jan (Frontiers in Psychology, 2018)
Studies in social perception traditionally use as stimuli frontal portrait photographs. It turns out, however, that 2D frontal depiction may not fully capture the full morphological diversity of facial features. Recently, 3D images started to become increasingly popular, but whether their perception differs from the perception of 2D has not been systematically investigated as yet. Here we investigated congruence in the perception of portrait, left profile, and 360° rotation photographs. The photographs were obtained from 45 male athletes under standardized conditions. In two separate studies, each set of images was rated for formidability (portraits by 62, profiles by 60, and 360° rotations by 94 raters) and attractiveness (portraits by 195, profiles by 176, and 360° rotations by 150 raters) on a 7-point scale. The ratings of the stimuli types were highly intercorrelated (for formidability all rs > 0.8, for attractiveness all rs > 0.7). Moreover, we found no differences in the mean ratings between the three types of stimuli, neither in formidability, nor in attractiveness. Overall, our results clearly suggest that different facial views convey highly overlapping information about structural facial elements of an individual. They lead to congruent assessments of formidability and attractiveness, and a single angle view seems sufficient for face perception research.